Organizational Politics and Deviance: Exploring the Role of Political Skill. Issue 2 (15th March 2019) - Crawford, Wayne S.; Lamarre, Esther; Kacmar, K. Michele; Harris, Kenneth J.
ABSTRACT: Building on social exchange theory, this study examines the relationship between perceptions of organizational politics and employee performance and interpersonal skills. We hypothesized that perceptions of organizational politics create an imbalance in the exchange relationship between employee and organization, which leads to organizational deviance. We also hypothesized that supervisors may attempt to rebalance the exchange relationship by providing lower performance and interpersonal skills ratings. Finally, we suggest that politically skilled employees avoid an increase in negative ratings. The present study demonstrates that perceptions of organizational politics may lead to negative employee behaviors and reduced supervisors' ratings in an effort to rebalance the exchange relationship. In addition, politically skilled employees may avoid increased negative ratings when politics perceptions are high.